The Influence of Deviden Policy, Funding Decisions and Investment Decisions on Company Value with ROE as an Intervening Variable in Industrial Sectors Listed on the Indonesian Stock Exchange - Tiara Putri; Fuad Ramdhan Ryanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the effect of funding decisions, dividend policies, and investment decisions on firm value, with Return on Equity (ROE) as an intervening variable in industrial sector companies listed on the Indonesia Stock Exchange (IDX). The industrial sector plays an important role in economic growth, but faces challenges such as falling profits and market pressures. This study uses an associative approach with secondary data collected through documentary studies from 62 industrial companies during 2021-2023. Data analysis includes classic assumption tests and path analysis. The results showed that funding decisions, dividend policy, and investment decisions have a very strong correlation with ROE. These variables, when mediated by ROE, show a stronger relationship to firm value. The F test shows that Dividend Policy, Funding Decisions, and Investment Decisions have a significant effect on ROE, while Dividend Policy, Funding Decisions, and Investment Decisions through ROE as intervening variables do not have a significant effect on the firm value variable. The t-test shows that partially, the dividend policy variable, funding decisions, have no partial effect on ROE, while investment decisions have a partial effect on ROE. Partially, the dividend policy variable, funding decisions, and investment decisions do not have a significant effect on the firm value variable through ROE. Future research is recommended to explore additional variables or use alternative analytical tools to gain more comprehensive insights.